KERAGAAN DUA BELAS VARIETAS UNGGUL BARU PADI PADA AGROEKOSISTEM LAHAN PASANG SURUT DI KALIMANTAN BARAT - Agus Subekti; Abdullah Umar (Agrica Ekstensia, 2022)
The population of West Kalimantan continue to grow from year to year, led to increasing need for major food crops, especially rice. Farmers of West Kalimantan cultivate rice in various land agro-ecosystems, one of which is tidal swamp. Problems faced by farmers in rice cultivation on tidal swam include waterlogging, high soil acidity, poor nutrients, saltwater intrusion, and Fe toxicity. One of the efforts that can be done to increase rice productivity on tidal swamp is the introduction of new high-yielding varieties of rice with high yield potential. The purpose of this trial was to determine the performance of twelve new superior varieties rice with high yield potential on tidal swamp in West Kalimantan. The trial used a Randomized Block Design (RBD). The treatments were twelve new high-yielding varieties, namely Inpara 10, Inpari 32, Inpari 39, Inpari 45, Inpari 47, Inpari 48, Digdaya, Padjadjaran, Cakrabuana, Gemah, Mantap, and Cisaat, with five replications. The variables observed were plant height, number of productive tillers, panicle length, number of filled grain per panicle, percentage of filled grain per panicle, and productivity. The data were analyzed by ANOVA and further tested with the Tukey's Honest Significant Difference test. The results showed that the new high-yielding varieties with good performance and suitable for development on tidal swamp in West Kalimantan is Padjadjaran with productivity of 5.6 t/ha.